Efficacy and safety of Lenvatinib-based combination therapies for patients with unresectable hepatocellular carcinoma: a single center retrospective study - Huang, Jian; Wang, Zhen-Guang; Tao, Qi-Fei; Yang, Yun; Yuan, Sheng-Xian; Gu, Fang-Ming; Liu, Hui; Pan, Ze-Ya; Jiang, Bei-Ge; Lau, Wan Yee; Zhou, Wei-Ping (Frontiers in Immunology, 2023)
Background: Reports on Lenvatinib-based therapies have shown promising treatment outcomes for patients with unresectable hepatocellular carcinoma (uHCC). However, the effect and safety of Lenvatinib-based therapies require further investigations. Methods: This retrospective, single-center study investigated the safety and treatment efficacy of Lenvatinib-based combination therapies for uHCC patients. The primary endpoints were progression-free survival (PFS) and overall survival (OS). The secondary endpoints were progressive disease (PD), stable disease (SD), partial response (PR), and complete response (CR). Results: A total of 91 patients (75 male and 16 female) with uHCC received systemic therapies based on Lenvatinib in our center. Of these, 46 (50.5%) received Lenvatinib combined with PD-1 antibody treatment and all, except for two, also underwent local therapy. The remaining 36 patinets received Lenvatinib combined with transcatheter arterial chemoembolization (TACE), while one patient treated Lenvatinib combined with radiotherapy and eight received Lenvatinib alone. After a median treatment time of eight months, the objective response rate (ORR) of the entire cohort was 58.2% (53 patients), including seven patients with CR and 46 patients with PR, while 21 patients (23.1%) had SD. The disease control rate (DCR) of all patients was 81.3% (74 patients). However, 17 patients (18.7%) developed PD. The 1-and 2-year cumulative OS rates for the entire cohort were 66.8% and 39.3%, respectively, while the corresponding PFS rates were 38.0% and 17.1%, respectively. Univariate and multivariate Cox regression analysis revealed that the presence of multiple tumor sites was an independent risk factor for poor OS in uHCC patients (HR=2.204, 95% CI=1.104-4.399, P=0.025). The most frequently reported adverse events in all patients were AST elevation (51.6%), followed by hypertension (33.0%), ALT elevation (26.4%), and decreased appetite (25.3%). After a combination treatment of Lenvatinib-based therapies, 15 patients met the criteria for salvage liver resection and underwent downstaging hepatectomy with curative intent. The combination with PD-1 treatment was minimally effective in improving the prognosis of uHCC patients treated with Lenvatinib combined with TACE.Our study demonstrated that a proportion of patients benefited from Lenvatinib-based combination therapies with manageable safety profiles, allowing these patients to undergo downstaging surgery with curative intent.